Aplicación de métodos ergonómicos para la efectividad organizacional en una empresa agroindustrial - Manrique Suárez, Luis Humberto (2022)
The objective of the research is to use ergonomic methods to improve internal processes, optimize organizational resources to achieve organizational effectiveness in an agro-industrial company. This is a case study, in which a medium-sized company with 50 workers was considered, it was carried out in one of the most representative companies in the food processing industry, because most of the companies dedicated to agribusiness handle very similar processes. We focus our research on physical ergonomics, taking the dimensions of the human body and evaluating work postures, overexertion, manual handling of materials, repetitive movements, musculoskeletal injuries of work origin, design of health and safety jobs. at work When applying ergonomic methods, the average score dropped by 17.39% from 11.5 to 9.25 points, in cutting-peeling, it was reduced from 12 to 7 and in selection there is also a reduction from 12 to 7, this means that the level Risk has dropped from very high to medium, there is also an increase in labor productivity of 1.95% from 339.7 kg / hh to 346.3 kg / hh. When taking measurements of the company's workers, 50% measure up to 1.68m, the seated height is 0.84 m, the height of the knees is 0.46 m, the width between coconut and elbow is 0.42 m. among others, that must be taken into account when designing workstations.